2011
DOI: 10.1021/nn2005443
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Radiation Damage and Edge Structures in Boron Nitride Membranes

Abstract: We show that hexagonal boron nitride membranes synthesized by chemical exfoliation are more resistant to electron beam irradiation at 80 kV than is graphene, consistent with quantum chemical calculations describing the radiation damage processes. Monolayer hexagonal boron nitride does not form vacancy defects or amorphize during extended electron beam irradiation. Zigzag edge structures are predominant in thin membranes for both a freestanding boron nitride monolayer and for a supported multilayer step edge. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…It was suggested that B atoms were knocked out to form such a kind of defects since the operating electron energy (80 keV) was close to the threshold energy (79.5 keV) to knock the B atoms out but far below that (118.6 keV) to knock the N atoms out . After 45 min (Figure c), some “nanoscrolls” appeared on the surface of the nanotube and more came out after 60 min (Figure d). Such “nanoscrolls” formed when the dangling part of the damaged walls peeled off during the irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that B atoms were knocked out to form such a kind of defects since the operating electron energy (80 keV) was close to the threshold energy (79.5 keV) to knock the B atoms out but far below that (118.6 keV) to knock the N atoms out . After 45 min (Figure c), some “nanoscrolls” appeared on the surface of the nanotube and more came out after 60 min (Figure d). Such “nanoscrolls” formed when the dangling part of the damaged walls peeled off during the irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…To-date, the majority of structural studies on 2D h-BN have focused on the edge structures, topological, point, and substitutional defects, [15][16][17][18][19][20] largely ignoring stacking sequence and their local variations. In this paper we have investigated the stacking sequences present in sheets of h-BN produced by liquid-phase exfoliation of bulk h-BN in common organic solvents.…”
mentioning
confidence: 99%
“…A subsequent study highlighted an instance where a hexagonal defect formed in multilayer h-BN, under similar electron irradiation conditions (Warner et al, 2010). Another report showed, through EWF studies, that the edges of the flakes had an equal probability of displaying B or N terminations, for both monolayer and multilayered areas (Kim et al, 2011). A recent study has shown that the polarity of the defects which are created in h-BN depends on the temperature (Cretu et al, 2015); here it was found that at high-temperature N atoms are preferentially removed, creating N vacancies and B-terminated tetravacancies.…”
Section: Discussionmentioning
confidence: 94%